Shrine enshrining images of Tirthankaras - Temples of India Project Team (Jio Institute, 2024)
Within the Adinatha Temple, there is a side shrine that enshrines images of Tirthankaras. This small subsidiary shrine is on the southern side of the main garbhagriha (sanctum sanctorum). A triumphal arch with three divisions, this small temple has three icons on a high pedestal, all sitting in padmasana (lotus pose).